Natural Outbreaks of Infectious Bursal Disease in Brahma and Aseel Chicken in Iraq - Qayssar Ali Kraidi (Journal of Global Pharma Technology, 2019)
The infectious bursal disease (IBD) represents one of the most severe poultry diseases and is responsible for marked economic losses in poultry populations in Iraq. Backyard chicken with different breeds have been recently raised successfully in a rural area for hobby and household consumption, however, the status of the disease in free-ranging backyard chickens in Iraq is not documented, for this reason, the objective of the present study was to determine the disease in free-range poultry naturally infected with IBDV currently circulating in Iraq. A tentative diagnosis of IBD was conducted based on clinical findings, gross lesions besides the histopathology and lesion scoring analysis and was confirmed by identification of IBDV antigen in AGPT. Typical IBD clinical signs and lesions were observed in all types of birds with a high mortality rate (30% & 25%) reported in Aseel and Brahma breeds, respectively. Histopathological lesion scores analysis for IBDV characterized by a high lesion score of (+5) observed in the studied birds of all breeds. Based on the results of high mortality rate and high histopathological lesion scores we can suggest the occurrence of the disease in backyard chicken in Iraq associated with pathogenic field IBD virus. The present study provides first background document on the current status of IBD in free-range poultry in Iraq.Keywords: Aseel, Brahma, IBD, Iraq.